Aspectos ecofisiológicos e morfometria da Curitiba prismatica (D. Legrand) Salywon & Landrum - Gardin, Edson (2017)
The ecophysiology of Curitiba prismatica (D. Legrand) Salywon and Landrum leaves was evaluated in a fragment of Mixed Ombrophilous Forest in faxinal system, in Rebouças Municipality, PR, Brazil. This study aimed at analyzing polyphase induction (OJIP curve) and slow kinetics of chlorophyll a fluorescence, besides quantifying photosynthetic pigment levels in trees developed under full sun and understory environments in the four seasons of the year. Chlorophyll a fluorescence was analyzed with data of slow and rapid kinetics in previously dark adapted leaves, between 2015 and 2016. The parameters Fo, Fm, Fv/Fm, ABS/RC, PIABS by the OJIP test, photosynthetic efficiency, and electron transport rate were evaluated. The observed Fo and Fm values were significantly different (p<0.05), with the highest values in trees under full sun. The effect of seasonality on C. prismatica trees under full sun showed significant differences (p<0.05) in the summer when compared to other seasons, resulting in a higher Fm value, probably due to damages caused by photooxidation. For understory C. prismatica trees, no significant differences were observed among seasons. In the winter, similar results were obtained in the two environments. Chlorophyll a, b and total levels were significantly different (p<0.05) between the two environments throughout all seasons, with the highest values observed in understory trees, which were less sensitive to seasonal variations of chlorophyll a fluorescence. This study indicates that C. prismatica showed adaptive changes according to the environment.